Corporate refocusing in the UK: an empirical investigation - Haynes, Michelle (1999)
It has been widely suggested that since the early 1980s the trend towards ever greater corporate diversification has been reversed in many mature economies; with many diversified firms narrowing the scope of their activities by refocusing on what are perceived to be core businesses primarily, though not exclusively, through major divestments. Whilst recent research, largely in the US context, has started to take place on corporate refocusing there is a paucity of evidence on refocusing in the UK. The aim of this thesis is to address this shortcoming and to examine corporate refocusing activity in the UK. This study uses a specially constructed data set compiled from primary and secondary sources, covering 158 publicly quoted companies over the period 1985 to 1993. The thesis initially examines the extent and nature of refocusing activity in the UK. It is found that refocusing activity is undertaken by a substantial majority of the sample firms. Firms refocused primarily by divesting unrelated businesses and acquiring related activities. The thesis proceeds to examine the characteristics of refocusing firms using cross-sectional OLS and logit techniques. It is found that refocusing firms are characterised by high levels of diversification, low levels of management ownership and to a limited extent by an attractive core business on which to refocus. The thesis next examines the determinants of firms' divestment behaviour using both crosssectional and panel data proportions and count data (Poisson and Negative Binomial regressions) techniques. The results indicate that divestment is a purposeful response to financial, strategic, corporate governance and - to a limited extent - market structure characteristics. In the final part of the thesis, we examine the impact of divestment on firm performance by adopting a dynamic profitability equation augmented with divestment variables. The results suggest that divestment has a positive impact on the profitability of divesting firms. The performance effect is greater for firms operating weak governance mechanisms. It is concluded that corporate refocusing is an important phenomenon in the UK and is not merely an invention of the business press. The determinants of divestment indicate that divestment is not simply a reflection of managerial idiosyncrasies or mean reversion behaviour in the activities undertaken, but a purposeful response to a change in the equilibrium level of diversification. The adoption of a refocusing strategy appears to improve the overall performance of divesting firms.